Non-localisation: a semiotic, economic and media investigation into Apple’s localisation strategy and its impact on Chinese translation traditions - Sun, Xiaofei (2016)
Situated at the crossroads of Translation Studies, Semiotics and Chinese Studies, this thesis examines the non-localisation (NL henceforth) strategy adopted by Apple for its official website. Website layouts, multi-media information, textual information, such as names of products, services and technological solutions are kept unchanged on the Chinese target-language website. Focusing on the non-localised features, this thesis has three major aims. First of all, it seeks to verify a foreignising impact of the NL strategy on the Chinese translation tradition and Sino-centric values. Secondly, it tries to reconcile translation studies with merits of the localisation industry, namely digital technology and industrial management. Thirdly, regarding global power struggles, this thesis aims to verify that the foreignness of currently ‘dominant’ Anglo-American cultures, NL, is still mediated by the ‘dominated’ Chinese system that has long been a culture centre itself. However, the Chinese system cannot keep its own culture untouched by foreignness either. In order to achieve these three aims, a framework built on semiotics, digital-media, socioeconomics was established, giving birth to the following critical findings. First, NL has a foreignising impact on the Chinese translation traditions. In terms of how this impact is achieved and its efficacy, NL is fundamentally different from Lawrence Venuti’s paradigmatic model in translation studies. Venuti’ suggests translators in target cultures should take the initiative to achieve a foreignising impact by only using target language codes, in the literary domain. On the contrary, NL’s foreignising impact is achieved through:1) Apple’s technological and linguistic control over the development and dissemination of NL items, (such as iPhone and iPad) into the Chinese target culture through digital media, which minimise interference from Chinese publishers and editors who are mainly powerful in print media; 2) In Charles Peirce’s terms, NL items, being source language codes, are signs signifying Apple products that function as objects ubiquitously available in both source and target cultures (e.g. iPhone, a verbal sign, signifies Apple smartphone, an object popular in both U.S. and China); thus, no target code is needed for NL items to be understood in China, highlighting immediate foreignness, with substantially reduced target semiotic mediations; 3) Consumerism which is a foreign-oriented dimension of the Chinese society, conflicts with China’s domestic-oriented translation traditions. Due to China’s booming consumerism, a large and continuous consumption of Apple products in China socially consolidates the foreignising impact, and this cultural impact becomes measurable. The second key finding is the relationship between localisation and translation, and the implication on translation studies. Addressing existing attempts to explore the relationship between localisation and translation, (i.e. ‘localisation is just specialised translation’ vs ‘localisation includes translation’) this thesis discovers that localisation and translation are merely two different text production methods. In other words, both have equal status. Text production method refers to the entire information creation and dissemination process between source and target cultures. The difference between the localisation and translation is the historical, media, and technological context in which both are developed. Drawing on a review of media history, the thesis reveals that translation, as a text production method, includes source text composition, source text selection, translator selection, translation, translation editing and publishing. As print media matured, translation publishers and editors in the target cultures took and continue to take control over almost everything of translation apart from source text composition. The domesticating power of the publishers in the Anglo-American world, pointed out by Venuti, is actually a natural result of the industrial development; accordingly, it’s not difficult to understand why translators’ initiative to challenge the domestication tradition has been difficult. Localisation, as another text production method, includes, source content development and internationalisation, source content rendition, finalisation, and target content release. Multinational high-tech companies like Apple takes control over the entire process of localisation, witnessing a major shift of power from target to the source. This power shift is one of the major propelling forces for NL’s foreignising impact on the Chinese context. The macro-structural differences between localisation and translation pointed out in this thesis have significant implications on the current understanding of how translation creates cultural impacts in academia i.e. what translators do textually, such as a change of language style for instance, is only a part of the entire text production process. Overall this thesis argues that the study of translation impact should include much more than texts per se; instead social-economic and industrial circumstances under which texts are produced and disseminated must be factored in too.